DRIP IRRIGATION TECHNOLOGY IS A TECHNOLOGY FOR GROWING TWO TYPES OF CROPS USING WATER AND LAND RESOURCES EFFICIENTLY - Umrbekovna, Matyaqubova Elmira; O‘rolovna, Mamatqulova Lobar; Gulamovich, Yulchiev Davronbek (Research Focus International Scientific Journal, 2026)
This article examines the technology of producing two types of crops in areas where drip irrigation technology is applied, with efficient use of water and land resources. The experiments were conducted with soil moisture maintained at 70–70–65% and 75–75–65% of field capacity. Total water consumption, use of soil moisture reserves, and irrigation efficiency were analyzed. The results showed that maintaining pre-irrigation soil moisture at 75–75–65% of field capacity significantly increased crop yield and water use efficiency. The highest yield (57.3 c/ha) was obtained in the 7 th treatment. The total water consumption for producing 1 centner of yield was 110.2 m³/c, indicating efficient use of water resources. The obtained results have important scientific and practical significance for optimizing irrigation regimes in intercropping systems.